2020
DOI: 10.1371/journal.pone.0244170
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of the Vietnamese during the COVID-19 pandemic

Abstract: Background Vietnam applied strict quarantine measures to mitigate the rapid transmission of the SARS-COV-2 virus. Central questions were how the COVID-19 pandemic affected health-related quality of life (HRQOL) of the Vietnamese general population, and whether there is any difference in HRQOL among people under different quarantine conditions. Methods This cross-sectional study was conducted during 1 April– 30 May 2020 when the COVID-19 pandemic was at its peak in Vietnam. Data was collected via an online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 14 publications
7
45
6
1
Order By: Relevance
“…It is therefore obvious that people with a higher level of income are less concerned about these items, and therefore they are expected to have higher utility levels. However, other studies conducted in the same period of Covid-19 did not report a signi cant relationship between income level and utility score [5,29]. Like our study, other studies showed that there is a signi cant inverse relationship between the level of anxiety about becoming infected by Covid-19 and the utility score [5].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…It is therefore obvious that people with a higher level of income are less concerned about these items, and therefore they are expected to have higher utility levels. However, other studies conducted in the same period of Covid-19 did not report a signi cant relationship between income level and utility score [5,29]. Like our study, other studies showed that there is a signi cant inverse relationship between the level of anxiety about becoming infected by Covid-19 and the utility score [5].…”
Section: Discussioncontrasting
confidence: 59%
“…This result is almost similar to the score (0.79) of the general population of Iran (using the Cross Walk method) before the Covid-19 pandemic [22]. And it was lower than the score reported in studies conducted before the Covid-19 pandemic in South Australia of 0.91 [23], Germany 0.92 [24], Poland 0.89 [25], Uruguay 0.95 [26], Italy 0.92 [27], and studies conducted during the Covid-19 epidemic in China 0.949 [5], Portugal 0.86 [28] and Vietnam 0.95 [29]. The difference in the value set generated by each country (due to differences in demographic characteristics as well as the type of calculation method) and differences in age and gender combination, and level of education, income, and type of study design can be reasons for differences in the utility scores in different studies.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Several studies have been recently published examining the impact of COVID-19 and public health control measures on the general Vietnamese population. These observational studies showed that the pandemic has had a significant impact on the overall well-being and mental health status of this population [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Several recently published studies have examined the impact of COVID-19 and public health containment measures in the Vietnamese population [12][13][14][15][16]. To our knowledge, no study has examined the impact of COVID-19 on patient's needs, health care seeking behaviors,…”
Section: Introductionmentioning
confidence: 99%